Value of Glut-1 and Koc Markers in the Differential Diagnosis of Reactive Mesothelial Hyperplasia, Malignant Mesothelioma and Pulmonary Adenocarcinoma - Ucer, Ozlem; Dagli, Adile Ferda; Kilicarslan, Ahmet; Artas, Gokhan (De Gruyter Open Ltd, 2013)
Objective: Malignant mesothelioma (MM) is a primary malignant tumor developing from mesothelial cells lining the serosal surfaces and particularly the pleura, and has a very poor prognosis. It may display a variety of histological patterns and has a wide spectrum of cytomorphological characteristics, causing problems in its differential diagnosis from lung adenocarcinomas and sometimes from benign mesothelial proliferations. Immunohistochemical examination is the most useful method for this distinction. In our study, we aimed to determine the value of glucose transporter isoform-1 (GLUT-1) and K homology domain-containing protein (KOC) markers in the differential diagnosis of reactive mesothelial hyperplasia, malignant mesothelioma and lung adenocarcinoma. Material and Method: Our study included 30 samples of malignant mesothelioma, 30 samples of pulmonary adenocarcinoma and 30 samples of reactive mesothelial hyperplasia selected from the archives of the Firat University Hospital's Pathology Department Laboratory. The samples were applied GLUT-1 and KOC markers by immunohistochemistry and the place of these markers in the differential diagnosis was examined. Results: GLUT-1 was found positive in 80% of malignant mesothelioma cases, 83.3% of adenocarcinoma cases and 6.6% of reactive mesothelial hyperplasia cases. KOC was positive in 83.3% of malignant mesothelioma cases, 76.6% of adenocarcinoma cases and 46.6% of reactive mesothelial hyperplasia cases. There was no statistically significant difference between malignant mesothelioma and lung adenocarcinoma cases in terms of the diffuseness and intensity of staining with GLUT-1, whereas a significant difference was established when these groups were compared with reactive mesothelial hyperplasia cases. However, the KOC staining diffuseness and intensity results were similar to those obtained with GLUT-1. Conclusion: In conclusion, GLUT-1 and KOC markers do not differentiate malignant mesotheliomas from pulmonary adenocarcinomas but can be useful in differentiating reactive mesothelial hyperplasia from malignant mesothelioma and lung adenocarcinoma.
Reaktif mezotel hiperplazisi, malign mezotelyoma ve akci?er adenokarsinomu ayırıcı tanısında glut-1 ve koc'un yeri
Keywords: Mesothelioma; Adenocarcinoma; Mesothelium; Glucose Transporter Type 1; IMP3 protein